Digital literacy of healthcare professionals in pharmacies - Andric, Sanja; Odalović, Marina (Archives of Pharmacy, 2022)
Professional standards require from healthcare professionals to possess a certain level of digital literacy. The aims of paper were: examination of the experience of healthcare professionals in pharmacies in the use of digital technologies, self-assessment of knowledge and skills, evaluation of attitudes and analysis of the needs for improvment of digital competencies. A special paper questionnaire was designed and used in the research, which was distributed to the pharmacy staff from AU “Benu“. 94,3% use digital technology at work every day, 89,8% of respondents using it for searching of medical and medicine information (89,8%). Only 9,7% of the respondents completed an additional formal program or course. Pharmacists assessed their digital literacy significantly higher than pharmaceutical technicians, 3,67±0,79 vs 3,44±0,63 (p